2021
DOI: 10.3390/ijerph18158210
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Endometriosis: A Brief Overview and Recommendations to Improve Psychosocial Well-Being and Diagnostic Delay

Abstract: Endometriosis is a chronic gynecological disease that affects approximately 1 in 10 women of reproductive age. Symptoms of severe pelvic pain, infertility, fatigue, and abnormal menstruation can cause significant negative effects on an individual’s physical and mental health, including interactions with their family, friends, and health care providers. Stigma associated with endometriosis has been under-studied and is rarely discussed in current literature. Herein, this paper aims to provide a brief overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 85 publications
(103 reference statements)
4
51
0
2
Order By: Relevance
“…Additional challenges emerge from considerable diagnosis delay, difficulty to fulfil the social role of motherhood and lack of family and social support due to condition misunderstanding (Sims et al, 2021). Those factors create a context of high psychological stress (Brasil et al, 2020), which interacts with the endometriosis pathophysiology (Cuevas et al, 2018) and pain in a vicious cycle pattern (de França Moreira et al, 2021; Toth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additional challenges emerge from considerable diagnosis delay, difficulty to fulfil the social role of motherhood and lack of family and social support due to condition misunderstanding (Sims et al, 2021). Those factors create a context of high psychological stress (Brasil et al, 2020), which interacts with the endometriosis pathophysiology (Cuevas et al, 2018) and pain in a vicious cycle pattern (de França Moreira et al, 2021; Toth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A range of physician-related [7,8] and patient-related factors [9] as well as stigmatization of the topic of menstruation by society have been identi ed [10,11]. The consequences of the disease being diagnosed late (or too late) on the course of disease, the quality of life and the costs of the disease have already been documented in studies [12,13].…”
Section: Abstract Backgroundmentioning
confidence: 99%
“…Various studies have shown that endometriosis reduces the quality of life of affected women [1,18,19] . In addition to having physical, mental and social consequences for affected women at the individual level [12], endometriosis is estimated to have signi cant economic impacts on society as a whole [20][21][22], due mainly to increased healthcare utilization and reduced work productivity [21,23,24] . Endometriosis is estimated to affect 4-10% of women of reproductive age, making it one of the most common benign gynecological conditions [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore decided to develop an internet-based CBT (iCBT) program. Such programs have previously been proven effective in the treatment of psychological [ 46 ] as well as psychosomatic [ 47 ] and somatopsychic [ 48 ] disorders and are considered as effective as face-to-face-therapy [ 49 , 50 ]. We hypothesize that endometriosis-related QoL will be significantly improved when patients take part in our iCBT training.…”
Section: Introductionmentioning
confidence: 99%